Development's invisible hands: Introduction to special issue - Thomas, Alan; Sumner, Andy; Tribe, Michael (Journal of International Development, 2009)
This Special Issue comes from the Development Studies Association (DSA) 30th Anniversary conference in 2008. The theme was ‘Development's Invisible Hands’, focusing on the forces likely to influence global change and re-shape development agendas over the next 30 years. The first section comprises brief invited thinkpieces mainly from DSA past presidents. Interestingly, while some focus on Adam Smith's original ‘invisible hand’ analogy and others discuss a range of non-market issues, several invoke Karl Polanyi on the limitations of market society. The second and third sections consist, respectively, of ‘synthesis’ papers on parallel panel themes and papers developed from the best panel presentations. The papers demonstrate the range of issues raised by questioning the future of development and development studies—while the limitations of future gazing are pointed up by the unexpected challenge to current development models presented since the conference by the global financial crisis. Copyright © 2009 John Wiley & Sons, Ltd.
Keywords: Development Studies Association; POLANYI, Karl, 1886-1964; SMITH, Adam, 1723-1790 - political & social views; development economics; development studies; economic development; futures; invisible hand; mathematical models of economics